Co-production in practice: How people with assisted living needs can help design and evolve technologies and services - Wherton, J; Sugarhood, P; Procter, R; Hinder, S; Greenhalgh, P (BioMed Central, 2015)
Background The low uptake of telecare and telehealth services by older people may be explained by the limited involvement of users in the design. If the ambition of ‘care closer to home’ is to be realised, then industry, health and social care providers must evolve ways to work with older people to co-produce useful and useable solutions. Method We conducted 10 co-design workshops with users of telehealth and telecare, their carers, service providers and technology suppliers. Using vignettes developed from in-depth ethnographic case studies, we explored participants’ perspectives on the design features of technologies and services to enable and facilitate the co-production of new care solutions. Workshop discussions were audio recorded, transcribed and analysed thematically. Results Analysis revealed four main themes. First, there is a need to raise awareness and provide information to potential users of assisted living technologies (ALTs). Second, technologies must be highly customisable and adaptable to accommodate the multiple and changing needs of different users. Third, the service must align closely with the individual’s wider social support network. Finally, the service must support a high degree of information sharing and coordination Conclusions The case vignettes within inclusive and democratic co-design workshops provided a powerful means for ALT users and their carers to contribute, along with other stakeholders, to technology and service design. The workshops identified a need to focus attention on supporting the social processes that facilitate the collective efforts of formal and informal care networks in ALT delivery and use